Rhombohedral phase high-entropy alloy of AlMnCuZnBi as a photo-Fenton catalyst for methyl orange degradation - Anuraag N.S.; Kumar U.; Pradhan S.; Shaw S.K.; Sharma A.; Sinha I.; Prasad N.K. (My University, 2025)
The formation of solid solutions with five or more elements having nearly equiatomic contributions termed as high entropy alloys (HEA), is recent strategy for the development of new materials. Such alloys have displayed superior properties than the conventional ones. The prepared alloys are generally face- or body-centered cubic structures with a few exceptions for orthorhombic and hexagonal close packed structure. In this, we report the synthesis of HEA of AlMnCuZnBi having rhombohedral crystal structure. The material was prepared by vacuum arc melting route. Both the diffractions (X-ray and electron) confirm its structure. The calculated thermodynamic empirical parameters e.g. ΔSmix, ΔHmix, δ, VEC and Ω even validate the feasibility of this single phase solid solution. The HEA had shown feeble ferromagnetic behaviour. The rhombohedral structured HEA may open up new possibilities for various emerging applications. The proposed HEA acted as a catalyst for photo-Fenton like reaction and could degraded methyl orange dye completely in 170 minutes. © 2024 Elsevier B.V.